2011
DOI: 10.2355/isijinternational.51.1682
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Emission during Hydrogen Charging of a Pipeline Steel

Abstract: Acoustic emission (AE) during hydrogen-induced cracking (HIC) of low-carbon pipeline steel immersed into H2S containing media was investigated aiming at discriminating between damage mechanisms and getting a better insight on the kinetics of damage. Two kinds of steel samples -sensitive and resistant to hydrogen induced cracking -were tested. Three different kinds of acoustic emission signals were discriminated by a cluster analysis involving either spectral shape recognition or parametric c-means classifier. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…It is enough to choose one between duration and counts because of the strong correlation. Therefore, duration, energy, peak frequency, and spectrum gravity were chosen as the main characteristics for signal discrimination, which is also consistent with others’ work [ 9 , 12 ].…”
Section: Results and Discussion About Signals Discriminationsupporting
confidence: 67%
See 3 more Smart Citations
“…It is enough to choose one between duration and counts because of the strong correlation. Therefore, duration, energy, peak frequency, and spectrum gravity were chosen as the main characteristics for signal discrimination, which is also consistent with others’ work [ 9 , 12 ].…”
Section: Results and Discussion About Signals Discriminationsupporting
confidence: 67%
“…This suggested that Type 1 signals are possibly from H 2 evolution because a large amount of small hydrogen gas bubbles were observed immediately after applying the current. At the same time, in light of the results of other researchers [ 9 , 10 , 11 , 12 , 22 , 23 ], signals from H 2 bubbles are of low frequencies. Therefore, signals of Type 1 are likely to be generated by H 2 evolution while those of Type 3 are from crevice corrosion.…”
Section: Results and Discussion About Signals Discriminationmentioning
confidence: 86%
See 2 more Smart Citations